Musykilātu Istikhdāmi al-ṣuwar fīy Ta’līmi Maharah al-Kalāmi Bimadrosah ‘Ainul Falāh al-Mutawasiṭah al-Islāmiyyah Gulu’ Gulu’ Sumenep-Madura-Jawa Timur - Segaf Baharun; Hasan, Ainul (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2022)
Really pictures can motivate students to talk and help them feel moved. However, after the researchers conducted observations and interviews with Arabic teachers at MTs. Ainul Falah Guluk-Guluk Sumenep, he found that some students felt bored, bored and lazy when practicing speaking Arabic, did not pay attention to the lesson and did not have the ability to speak Arabic even though the teacher used colorful media in learning speaking skills. Therefore, researchers want to know how to use picture media and its problems in teaching speaking skills at the school. The formulation of the problems in this study are: (1) What is the process of using media images in teaching speaking skills at MTs. Ainul Falah Guluk-Guluk Sumenep Madura, East Java? (2) What are the problems faced by the teacher when using media images in teaching speaking skills at the school? (3) What is the solution to overcome these problems? In this study using descriptive research methods and qualitative approaches. Data collection techniques are interviews, observation and documentation. Whereas in data analysis, namely data reduction, data presentation and data verification. As for the research results, the researcher can summarize them as follows: (1) The process of using pictures in learning speaking skills at MTs. Ainul Falah is divided into three stages, namely introduction, core and closing. (2) The problems faced by the teacher when using media images in teaching speaking skills at the school are (a) the size of the images used is not large, (b) the images used are not clear. (3) The solution to overcome this problem is that the size of the image used must be in accordance with the number of students, the quality of the printed image must be good and satisfying, and the teacher should display the image through the LCD projector.